Finite Element Analysis of Optimal Control Problem Governed by Stokes Equations with $L^2$-Norm State-Constraints (Journal of Computational Mathematics, 2018)
An optimal control problem governed by the Stokes equations with $L^2$-norm state constraints is studied. Finite element approximation is constructed. The optimality conditions of both the exact and discretized problems are discussed, and the a priori error estimates of the optimal order accuracy in $L^2$-norm and $H^1$-norm are given. Some numerical experiments are presented to verify the theoretical results.